2006
DOI: 10.1111/j.1601-5037.2006.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a school‐based caries preventive program: a 4‐year study

Abstract: This longitudinal study aimed at testing the efficacy of a school-based caries preventive program, by comparing dental caries status of two groups, a study group (436 children) and a control group (420 children) over a period of 4 years. The study group received a preventive program which consisted of intensive oral hygiene instructions sessions, and supervised daily tooth brushing using fluoridated tooth paste in schools. The control group received only oral hygiene instructions sessions. Annual dental examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 7 publications
4
34
0
1
Order By: Relevance
“…The characteristics of the interventions in the included studies are summarized in Table . The trials were carried out in Jordan, Brazil, Germany and USA. In all trials, supervised toothbrushing was performed at schools but they differed regarding children's age, F concentration in the toothpaste and risk of caries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics of the interventions in the included studies are summarized in Table . The trials were carried out in Jordan, Brazil, Germany and USA. In all trials, supervised toothbrushing was performed at schools but they differed regarding children's age, F concentration in the toothpaste and risk of caries.…”
Section: Resultsmentioning
confidence: 99%
“…Participants were 2–14 years old, and one trial included only preschool children. Toothbrushing was performed with no F toothpaste, 500 ppm F toothpaste and 1000 ppm F toothpaste. Different follow‐up periods were reported: 21 months, 27–29 months, 3 years and 4 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequent brushing with fluoride toothpaste is an effective method to prevent caries in the permanent teeth of children and adolescents . More recent studies have reported that frequent brushing with fluoride toothpaste is important in controlling caries among adolescents .…”
Section: Discussionmentioning
confidence: 99%